Parental Misperception of Their Child's Body Weight Status Impedes the Assessment of the Child's Lifestyle Behaviors - Marie-Eve Mathieu; Vicky Drapeau; Angelo Tremblay (Hindawi Limited, 2010)
Objectives. To examine if distinct characteristics are associated with parental misclassification of underweight (UW), normal weight (NW), and overweight or obese (OWOB) children and the implications of misclassification on the parental evaluation of the child's lifestyle habits. Methods. Cross-sectional analysis (2004 sample) of the Quebec Longitudinal Study of Child Development (1998-2010) (n=1,125). Results. 16%, 55%, and 77% of NW, UW and OWOB children were perceived inaccurately, respectively. Misperception was significantly higher in nonimmigrant parents of UW children, in highly educated parents of NW children and in NW and OWOB children with lower BMI percentiles. Erroneous body weight status identification impedes the evaluation of eating habits of all children as well as physical activity and fitness levels of UW and OWOB children. Conclusion. Parental misclassification of the child's body weight status and lifestyle habits constitutes an unfavorable context for healthy body weight management.